The Heihe Integrated Observatory Network: A Basin‐Scale Land Surface Processes Observatory in China. Issue 1 (13th December 2018) - Liu, Shaomin; Li, Xin; Xu, Ziwei; Che, Tao; Xiao, Qing; Ma, Mingguo; Liu, Qinhuo; Jin, Rui; Guo, Jianwen; Wang, Liangxu; Wang, Weizhen; Qi, Yuan; et al.
Abstract : Core Ideas: Heihe was the first basin‐scale integrated observatory network established in China. An intensive flux observation matrix experiment was conducted. New techniques, e.g., wireless sensor network, flux matrix, and airborne remote sensing, are used. The integrated observatory network is useful in land surface processes research. Research on land surface processes at the catchment scale has drawn much attention over the past few decades, and a number of watershed observatories have been established worldwide. The Heihe River Basin (HRB), which contains the second largest inland river in China, is an ideal natural field experimental area for investigation of land surface processes involving diverse landscapes and the coexistence of cold and arid regions. The Heihe Integrated Observatory Network was established in 2007. For long‐term observations, a hydrometeorological observatory, ecohydrological wireless sensor network, and satellite remote sensing are now in operation. In 2012, a multiscale observation experiment on evapotranspiration over heterogeneous land surfaces was conducted in the midstream region of the HRB, which included a flux observation matrix, wireless sensor network, airborne remote sensing, and synchronized ground measurements. Under an open data policy, the datasets have been publicly released following careful data processing and quality control. The outcomes highlight the integrated research on land surface processes in the HRB and include observed trends, scaling methods, high spatiotemporal resolution remote sensing products, and model–data integration in the HRB, all of which are helpful to other endorheic basins in the "Silk Road Economic Belt." Henceforth, the goal of the Heihe Integrated Observatory Network is to develop an intelligent monitoring system that incorporates ground‐based observatory networks, unmanned aerial vehicles, and multi‐source satellites through the Internet of Things technology. Furthermore, biogeochemical processes observation will be improved, and the study of integrating ground observations, remote sensing, and large‐scale models will be promoted further.